Proceedings of 2nd International Conference on Communication, Computing and Networking ICCCN 2018, NITTTR Chandigarh, India - Krishna, C. Rama.; Dutta, Maitreyee; Kumar, Rakesh; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book provides insights from the 2nd International Conference on Communication, Computing and Networking organized by the Department of Computer Science and Engineering, National Institute of Technical Teachers Training and Research, Chandigarh, India on March 29-30, 2018. The book includes contributions in which researchers, engineers, and academicians as well as industrial professionals from around the globe presented their research findings and development activities in the field of Computing Technologies, Wireless Networks, Information Security, Image Processing and Data Science. The book provides opportunities for the readers to explore the literature, identify gaps in the existing works and propose new ideas for research.
Experimental Analysis of DDoS Attacks on OpenStack Cloud Platform -- Preserving User Location Privacy in Era of Location Based Services: Challenges, Techniques and Framework -- Performance Evaluation of LEACH Protocol Based on Data Clustering Algorithms -- A Survey On Wireless Sensor Networks Coverage Problems -- BATMAN: Blockchain based Aircraft Transmission Mobile Ad-hoc Network -- Fuzzy AHP based Technique for Handover Optimization in Heterogeneous Network -- Traffic heterogeneity analysis in an energy heterogeneous WSN routing algorithm -- A Comparative Analysis of Various Image Segmentation Techniques -- A Novel Approach of Optic Disc Detection for Diagnosis of Diabetic Retinopathy -- Medical Fusion Of Clahe Images Using Swt And Pca For Brain Disease Analysis -- Correction of segmented lung boundary for inclusion of injured diffused regions from chest HRCT images -- SREF Interest Measure based Classification to Extract Important Patterns -- Study of NoSQL Databases for Storing and Analyzing Traffic Data -- Approximate Computing for Machine Learning -- Diagnosis of Malignant Pleural Mesothelioma using KNN -- An Improved Automated Question Answering System from Lecture Videos -- Analyzing Behavior of ISIS and Al-Qaeda Using Association Rule Mining -- Digital Assessment of Spatial Distribution of the Surface Soil Types using Spatial (Texture) Features with MLC and SVM approaches -- Recommender System Survey: Clustering To Nature Inspired Algorithm -- Craniofacial Model Generation Using CAD/CAM Software -- The Effect of Various Parameters on the nozzle diameter and 3D printed Product in Fused Deposition Modelling: An Approach -- Computational Technique for onset of P-wave for Seismic Alert System -- Identification and classification of water stressed crop using Hyperspectral data: A Case study of Paithan Tehsil -- Distributed Mutual Exclusion Algorithm With Improved Performance -- Recent Trends in Green Cloud Computing -- Issues in Software Defined Networking -- Analyzing Privacy Issues InCloud Computing Using Trust Model.
Keywords: Telecommunication; Big data; Artificial intelligence; Communications Engineering, Networks; Big Data; Artificial Intelligence